Pengaruh Cat Stretch Exercise Terhadap Penurunan Intensitas Nyeri Menstruasi (Dysmenorrhea) dan Tanda-Tanda Vital pada Remaja - Purwaningsih Purwaningsih; Ni Ketut Alit Armini; Agus Sulistyono; Esti Yunitasari; Mira Triharini; Anita Nurmasitoh (Jurnal Ners, 2007)
Menstruation is a period of uterine fluid discharge to endometrial detachment, often accompanied with pain called dysmenorrhea. The objective of this study was  to  analyze the effect of cat stretch exercise on the relief of menstrual pain and characteristics of vital sign in adolescence. Pre experimental design (one group pre-post test) was used in this study, 12 samples were recruited by purposive sampling. Observation and questionnaire were applied to measure patient’s pain scale. Data were analyzed by  using  Wilcoxon signed rank test (p<0.05). Conclusion: the cat stretch exercise has effect on relieve of menstrual pain (dysmenorrhea) and normalized of vital sign: blood pressure, hearth rate and respiratory rate.